Benefits of Rural Biogas Implementation to Economy and Environment: Boyolali Case Study - Tazi Hnyine, Zakaria; Sagala, Saut; Lubis, Wahyu; Yamin, Dodon (Universitas Muhammadiyah Surakarta, 2015)
Selo, a small agricultural-based village in Boyolali, Central-Java, Indonesia has initiated small-scale rural biogas adoption as it presumably reduces the consumption of LPG, firewood, chemical fertilizer and (womenâs) overall workload, which especially suitable due to the relatively high use of cattle in that area As environmental problems such as global warming from fossil fuel consumption and land degradation from deforestation and overuse of chemical fertilizers, and socio-economic problems as gender empowerment and self-sufficiency are becoming more pressing, it is useful to analyse the benefits of biogas as an alternative renewable energy technology (RET) provision in rural areas. This paper aims to assess the benefits of rural biogas adoption from an economic perspective, through calculating the direct and indirect benefits obtained from biogas adoption in Selo. For this, a field survey was carried out in Selo to ask questions to biogas users (N=21) and non-users (N=5) on their energy and fertilizer consumption, as well as emissions reductions resulting from biogas adoption. Based on the analysis, oon average, a household with biogas saves 490 kWh monthâ1, 20,000 IDR monthâ1,185 kg CO2e monthâ1.Chemical fertilizer consumption remains remarkably high, which may due to a lack of awareness on the potential of digester slurry by the farmers, for indeed, reduction of chemical fertilizer use would help address some environmental problems. Biogas quality of one household has also been determined by comparing its heating value to that of methane; the methane percentage (MP) was approximately 31%. The quality is considerably lower than expected from the literature (i.e. around 60%), which may be due to the farmers neither mixing nor supplying water to the dung. Trainings providing methods for improving digester overall effectiveness to particularly the women-folk may enhance digester management and thus biogas production, as they form the main primary operatives. Despite the room for improvement, the existing results clearly show that biogas adoption significantly reduces greenhouse gas (GHG) emissions, household energy costs, workload, improves environmental conditions and generates income through carbon credit exchange. Therefore, under the notions of sustainable development, environmental preservation and self-sufficiency, policy makers and NGOs should expedite their support in biogas development, e.g. by providing subsidies and awareness raising.